THE EFFECTIVENESS OF ICE-BREAKER ACTIVITY TO IMPROVE STUDENTS' SPEAKING SKILL - Alfian, Heri; Kaimuddin; Azis, Awalia (elstic : english language linguistics culture, 2023)
This research was aimed at investigating the effectiveness of Ice-Breaker Activity in improving students’ Speaking skill. A quasi experimental design was employed with two classes of the eighth graders at one school in Paccinongang, Gowa selected with total sampling as sample. The data were obtained through a pre-test, a post-test and an questionnaire. The Speaking assessment was covering pronunciation, vocabulary, grammar, fluency and self-confidence. The findings were analyzed statistically using independent t-test procedure. The findings shown that the value of t-test in experimental class was higher than the value of t-table(value of t 3,57 > value of t table 2.021). Furthermore, the students‘ perception towards Ice-Breaker Activity was 95,2% students agreed that this technique could help them to increse their Speaking skill. The statistical computation shown that Ice-Breaker Activity was not effective in improving the students’ Speaking skill but the students have positive perception towards the used of Ice-Breaker Activity. Designing the learning purpose appropriately which considers students’ needs and language level may ease teachers to use the the Ice-Breaker Activity in improving students’ Speaking skill. The teachers may try to take advantage of Ice-Breaker Activity to be utilized in their classroom activities to conduct an effective and interesting learning atmosphere in the classroom. Key words: Ice-Breaker activity, teaching speaking, junior high school